An investigation of parental non-involvement in the governance of a Duncan Village school and its implications for the management of the school : a case study - Ndlazi, Sibongile Mandisa (Rhodes University, Faculty of Education, Department of Education, 2000)
This study explores the perceptions that parents have about their non-involvement in the governance of a Duncan Village High School, and considers the implications of such perceptions for the management of the school. Recent discussions on Radio Talk Shows and articles written in local newspapers indicate that Black parents have generally not been involved in the education of their children at the traditionally Black schools. Parental non-involvement also emerges as a strong theme in recent research. However, most of the research and media coverage focuses on school management's perceptions of the reasons and consequences of such non-involvement. The parents' voices have rarely been heard. Against this background, as well as the fact that the South African Schools Act presents a strong case for the involvement of parents in school governance and management, a phenomenological investigation was conducted at a traditionally Black Duncan Village High School. I chose phenomenology because I believed this approach has the potential for revealing my respondents' attitudes and perceptions. The sample consisted of four parent members of the school governing body who were key informants. The respondents were subjected to unstructured interviews which were held at their homes. The interviews probed the background and reasons for their lack of involvement, and the possible implications ofthis non-involvement for school management. The most significant of the wealth of findings is that parental non-involvement is linked to the historical background of the culture of non-participation of Black people which was created and encouraged by the successive White Governments in South Africa.
Keywords: School management and organization -- South Africa -- Eastern Cape; Education -- Parent participation -- South Africa; Education -- Parent participation -- Case studies